IMPRESSIONS ABOUT THE COVID-19 PANDEMIC AND BONE MARROW TRANSPLANTATION - Paton, Eduardo (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
Covid-19 pandemic and Bone Marrow Transplantation